Marine oil pollution in Southeast Asia - Bilal, J. (South China sea fisheries development and coordinating programme, 1980)
This project on assessment of oil pollution and its impact on living aquatic resources in East Asia was decided to be started with an inventory of the present situation, i.e. a preparatory phase of getting acquainted,...